(untitled) (Journal of the College of Basic Education, 2022)
Image processing science reached today a very special standing. It is one of the modern and important applications in many fields. The research aims to design and build algorithms for image classification using Vector Quantization technique (VQ) and Neural Network (N.N).In the first stage of this work the data are collected from (30) different images. It is required that these images to be segmented into matrix of (8×8) dimension. These segments will be used collectively in the generation of reference sets for the purpose of classification.